Determinação das concentrações sanguíneas de pirazinamida em pacientes com tuberculose pulmonar - LUCENA, Stefania de Medeiros Araújo (Universidade Federal do Pará, 2019)
Tuberculosis is an important health problem in Brazil. The first-line treatment regimen adopted by the Ministry of Health for the treatment of the disease consists of rifampicin, isoniazid, pyrazinamide and ethambutol in the intensive phase (02 months), and rifampicin and isoniazid in the maintenance phase (04 months) of the treatment. The determination of the concentrations of these drugs in biological fluids is determinant to confirm the adequate exposure, besides helping to identify the causes of the multiresistance. In Brazil, the concentrations of these drugs have not yet been described in the course of treatment of the disease. Therefore, this study aims to determine the blood concentrations of pyrazinamide in patients with clinical and laboratory diagnosis of pulmonary tuberculosis, evaluating the influence of sex and hyperglycemia on the plasma levels of these drugs. For this, 54 adult patients of both sexes, diagnosed with active pulmonary tuberculosis, submitted to the first line treatment were included in the study, from which blood samples were collected before treatment (D0), at the end of the first month (D30) and at the end of the second month of treatment (D60). Patients' socio-demographic data were collected through a questionnaire. Pyrazinamide concentrations were determined by high performance liquid chromatography with ultraviolet detection and glycemia by conventional spectrophotometric method. Of the patients included in the study, 53% are male and 90% are between 19 and 59 years old. In addition, 37% completed only elementary education. Eight patients were excluded by noncompliance. The mean plasma concentration of pyrazinamide in pre-dose samples was 3.4 μg / mL and in the post-dose samples it was 72.5 μg / mL. These data point to adequate exposure of M. tuberculosis to the drug. Patients' sex did not influence plasma pyrazinamide concentrations. These results allow us to conclude that the doses of pyrazinamide used in tuberculosis patients caused by M. tuberculosis ensure effective therapeutic blood concentrations in post-dose samples, as well as the pre-dose concentrations were consistent with the pharmacokinetics of the drug. Finally, post-dose concentrations were significantly higher in patients with hyperglycemia.